Type 1 diabetes management and outcomes: A multicenter study in Thailand. Issue 4 (4th October 2020) - Dejkhamron, Prapai; Santiprabhob, Jeerunda; Likitmaskul, Supawadee; Deerochanawong, Chaicharn; Rawdaree, Petch; Tharavanij, Thipaporn; Reutrakul, Sirimon; Kongkanka, Chawkaew; Suprasongsin, Chittiwat; Numbenjapon, Nawaporn; Sahakitrungruang, Taninee; Lertwattanarak, Raweewan; et al.
Abstract: Aims/Introduction: The Thai Type 1 Diabetes and Diabetes Diagnosed Before Age 30 Years Registry, Care and Network was established in 2014 and involved 31 hospitals. The objective of the registry was to evaluate glycemic control and complications of patients with type 1 diabetes. Materials and Methods: Patients' demographics, clinical data, frequencies of daily self‐monitoring of blood glucose (SMBG), glycemic control and complications were collected. Results: Among the 1, 907 type 1 diabetes patients, the mean age was 21.2 ± 11.3 years. The mean glycated hemoglobin level was 9.35 ± 2.41%, with significant variations among age groups ( P < 0.001). Conventional insulin treatment and intensive insulin treatment were used in 43 and 57% of patients, respectively. Mean glycated hemoglobin levels were significantly higher in patients treated with conventional insulin treatment compared to those treated with intensive insulin treatment (9.63 ± 2.34 vs 9.17 ± 2.46%, P = 0.002). Compared to the conventional insulin treatment group, significantly more patients in the intensive insulin treatment group achieved good glycemic control ( P < 0.001), and fewer had diabetic retinopathy ( P = 0.031). The prevalence of microvascular complications increased significantly with age ( P < 0.001). Multivariate analysis showed good glycemic control to be associated with age 25 to <45 years, intensive insulin treatment with SMBG three or more times daily and diabetes duration of 1 to <5 years. Conclusions: Most Thai type 1 diabetes patients were not meeting the recommended glycemic target. As a result of this study, the national program to improve the quality of diabetes treatment and education has been implemented, and the results are ongoing. Abstract : This study reflects a nationwide snapshot of the management and outcomes of 1, 907 patients with type 1 diabetes in Thailand. A total of 43% of patients were found to be receiving conventional insulin treatment, and 57% were receiving intensive insulin treatment. Most of the Thai type 1 diabetes patients that we enrolled in this study were not meeting their recommended glycemic target. Good glycemic control was achieved by just 13% of patients receiving conventional insulin treatment, and by just 19% of patients receiving intensive insulin treatment. Multivariate analysis showed good glycemic control to be significantly associated with the 25 to <45 years age group, intensive insulin therapy with self‐monitoring of blood glucose three or more times daily and duration of disease of 1 to <5 years.